2017
DOI: 10.1177/1541931213601792
|View full text |Cite
|
Sign up to set email alerts
|

Graphic vs. Text-Only Résumés: Effects of Design Elements on Simulated Employment Decisions

Abstract: Résumés sometimes contain graphical elements, and the use of such “graphical résumés” may be increasing. The purpose of this study was to compare the effect of including different types of graphical elements in a résumé on the most important outcome measure from the perspective of the applicant – the probability of a positive selection decision by the evaluator. There was a reliable preference for a textual résumé when participants asked which design they thought would be most effective. However, there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…• • Format and design, such as color, fonts, graphics, or the one-page rule (e.g., Arnulf et al, 2010;Blackburn-Brockman & Belanger, 2001;Diaz, 2013;Guffey & Loewy, 2013, 2019Hart-Davidson, 1996;Johnson-Sheehan, 2011;Popham et al, 2017) • • Tone and phrasing, including keywords and spelling (e.g., Bennett, 2014;Boettger & Emory Moore, 2018;Charney et al, 1992;Diaz, 2013;Larsen, 2005;Martin-Lacroux & Lacroux, 2017;Ross & Young, 2005; Yate, 2016) • • Sections and their organization, such as skills and objective statements (e.g., Brown & Campion, 1994;Cole et al, 2007;Hutchinson & Brefka, 1997;Knouse, 1994;McKinney et al, 2003;Tsai et al, 2011) • • Items and activities that go into sections, such as internships, extracurricular activities, GPA, or employment gaps (e.g., Darolia et al, 2015;Nemanick & Clark, 2002;Nunley et al, 2016;Quadlin, 2018;Stout & Olson-Buchanan, 2018;Waung et al, 2017;Weisshaar, 2018) Even scholarship that explores larger concepts, such as Popken's (1992Popken's ( , 1993 work on the rhetoric of résumés, focuses on formal features: Popken (1992) pointed to the sections and items of a résumé as potentially exclusionary. Studies on formal features are one component for guiding applicants to create effective, audience-centered résumés.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…• • Format and design, such as color, fonts, graphics, or the one-page rule (e.g., Arnulf et al, 2010;Blackburn-Brockman & Belanger, 2001;Diaz, 2013;Guffey & Loewy, 2013, 2019Hart-Davidson, 1996;Johnson-Sheehan, 2011;Popham et al, 2017) • • Tone and phrasing, including keywords and spelling (e.g., Bennett, 2014;Boettger & Emory Moore, 2018;Charney et al, 1992;Diaz, 2013;Larsen, 2005;Martin-Lacroux & Lacroux, 2017;Ross & Young, 2005; Yate, 2016) • • Sections and their organization, such as skills and objective statements (e.g., Brown & Campion, 1994;Cole et al, 2007;Hutchinson & Brefka, 1997;Knouse, 1994;McKinney et al, 2003;Tsai et al, 2011) • • Items and activities that go into sections, such as internships, extracurricular activities, GPA, or employment gaps (e.g., Darolia et al, 2015;Nemanick & Clark, 2002;Nunley et al, 2016;Quadlin, 2018;Stout & Olson-Buchanan, 2018;Waung et al, 2017;Weisshaar, 2018) Even scholarship that explores larger concepts, such as Popken's (1992Popken's ( , 1993 work on the rhetoric of résumés, focuses on formal features: Popken (1992) pointed to the sections and items of a résumé as potentially exclusionary. Studies on formal features are one component for guiding applicants to create effective, audience-centered résumés.…”
mentioning
confidence: 99%
“…Research has demonstrated that employers do not agree on what constitutes "effective" formats, items, or organization (Boettger & Emory Moore, 2018;Camp et al, 2014;Pan et al, 2002;Ross & Young, 2005). Popham et al (2017) found that "there was not a statistically reliable difference in the effects of résumé design on hiring decision or confidence in that decision" (p. 1246). These results suggest that employers use more holistic and complex criteria than what happens at the level of items, format, organization, or design.…”
mentioning
confidence: 99%
See 1 more Smart Citation